JavaScript foundations course (Packt Publishing, 2023)
JavaScript is the driving force behind interactive web experiences, with every element on a website brought to life by its magic. It is key to understanding modern web applications and working in web design or development. In this course, you will embark on an exciting journey of learning and discovery. Starting with outputting strings and values, you will progress smoothly to working with variables and mastering decision-making using conditional statements. As you delve deeper, you will explore the might of loops, harness optimized data structures such as Sets and Maps, and handle JavaScript events with finesse. With each step, you will gain confidence in handling audio and video elements, manipulating data with fetch(), parsing JSON, and processing XML. Moreover, you will unlock the power of Promises and Async/Await, enhance string manipulation skills, and simplify string handling with templates. The adventure continues with classes and objects, creative projects with the canvas, and dynamically creating HTML elements. As the course nears its end, you will proudly showcase your newfound expertise in the JavaScript Final Project. By the end of this course, you will have transformed into a confident and proficient JavaScript developer, equipped with the knowledge and skills to create dynamic web applications. What You Will Learn Understand the building blocks for JavaScript output, variables, and math Master decision-making techniques with conditionals and switch...case Harness the power of loops with While, Do...While, and For Discover the versatility of arrays for organizing and manipulating data Interact with multimedia elements like audio and video Fetch the data and work with JSON and XML files Audience This course is designed for anyone who wants to create websites or other digital media. Whether you are a budding designer, aspiring developer, passionate teacher, eager student, or simply hungry for digital prowess, this course is tailor-made for you. Unlock the doors to JavaScript and front-end development with a basic knowledge of HTML and CSS. All you need is a passionate zeal to learn and explore the vast and exciting fields of JavaScript. About The Author Framework Tech, Mark Lassoff: Framework Tech, founded by the visionary Mark Lassoff, specializes in teaching digitally accessible technical skills to people just getting started in their technical careers, including web development, digital design, and other career paths enabled by technology. Framework Tech has bridged the gap between entertainment and education, creating a unique, immersive learning experience that resonates with students. Their instructors are more than just tech-savvy professionals; they are educators first and foremost, handpicked for their unique ability to translate complex technological concepts into digestible, engaging lessons. Framework Tech continues to evolve, constantly innovating to stay at the forefront of the online learning landscape.
"Published in August 2023.". - Online resource; title from title details screen (O'Reilly, viewed September 19, 2023)
Keywords: JavaScript (Computer program language); Streaming video; Internet videos; Vidéo en continu; Vidéos sur Internet; JavaScript (Langage de programmation); streaming video; Instructional films; Nonfiction films; Films de formation; Films autres que de fiction